THE ROLE OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN EMPLOYMENT - Khayrullo Bozorov; Ismoilov Ravshanjon Bakhriddinovich; Boltabaev Dilmurod Abdurashidovich (International Engineering Journal For Research & Development, 2020)
The article outlines the capability of small business to increase labor force participation and the theoretical foundation of impact of small business on supply and demand equilibrium of the labor force and on an increase of income per capita. The article also outlines several recommendations to stimulate small businesses participation in employment creation.